Strategy for Selection of Imported Glasses Suppliers for Retail Business Using Analytical Hierarchy Process (AHP) (Study at Metro Optics) - Yuanisa, Gendis (Jurnal Multidisiplin Indonesia, 2024)
Glasses are one of the products that have a large market in Indonesia, this has caused Indonesia to be flooded with imported glasses products, where China occupies 90% of the supply of imported glasses in Indonesia. As a business with a large market, Optik Metro plays a role in the imported glasses business. Its large monthly turnover of up to 40 to 60 million demonstrates its success. Optik Metro is currently collaborating with two imported glasses Suppliers, namely PT A, which distributes glasses from Japan, and PT B, which distributes glasses from China. Optik Metro has trusted its supply of goods from these two Suppliers for 10 years. However, over time, these Suppliers were found to have made mistakes that caused Optik Metro to suffer losses, such as delays in the arrival of goods and many products that were found to not meet the requirements or were defective. The length of Optik Metro's cooperative relationship with glasses suppliers PT A and PT B has led Optik Metro to announce delays and defects in imported glasses. However, if this phenomenon is unchecked, large losses may occur and have fatal consequences if the Supplier's performance is not effective and efficient. Supplier selection is one part of Operations Management, namely supply chain management, closely related to distributing products to consumers. Selecting the best-imported eyewear Supplier can be assisted with the Analytical Hierarchy Process (AHP) as a method for selecting Suppliers based on seven criteria determined by the company.